2023
DOI: 10.2217/fon-2022-0861
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of immune checkpoint inhibitors combined with recombinant human endostatin and chemotherapy as the first-line treatment of advanced non-small-cell lung cancer

Abstract: Background: To assess the efficacy and safety of combination of PD-1 inhibitors, recombinant human endostatin (Rh-endostatin) and chemotherapy as first-line treatment for advanced non-small-cell lung cancer (NSCLC). Methods: A total of 100 patients with advanced NSCLC were retrospectively reviewed and analyzed (58 in the group receiving PD-1 inhibitors plus Rh-endostatin and chemotherapy; 42 in the group receiving Rh-endostatin and chemotherapy). The primary end point was progression-free survival. Results: Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Notably, one case study reported that the addition of endostatin to PD-1 inhibitors and chemotherapy yielded significant results in treating stage IV LUSC ( 18 ). Furthermore, the combination has been attributed with promising efficacy and acceptable safety in the primary treatment of advanced NSCLC ( 10 , 19 ). Consequently, our retrospective analysis scrutinized the efficacy and safety of PD-1 inhibition with chemotherapy, both with and without the addition of endostatin, in stage IV LUSC treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, one case study reported that the addition of endostatin to PD-1 inhibitors and chemotherapy yielded significant results in treating stage IV LUSC ( 18 ). Furthermore, the combination has been attributed with promising efficacy and acceptable safety in the primary treatment of advanced NSCLC ( 10 , 19 ). Consequently, our retrospective analysis scrutinized the efficacy and safety of PD-1 inhibition with chemotherapy, both with and without the addition of endostatin, in stage IV LUSC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Endostatin (recombinant human vascular endostatin), targeting the endothelial cells of tumor vasculature, inhibits neovascularization, thereby impeding nutrient supply to tumor cells and curbing their proliferation and metastasis ( 9 ). As an anti-angiogenic agent, endostatin influences the tumor immune microenvironment similarly to PD-1 inhibitors, providing a rationale for their concurrent use ( 9 , 10 ). A retrospective clinical study has demonstrated that the combination of ICIs with endostatin offers greater efficacy and safety than the combination of ICIs with chemotherapy in treating advanced non-small cell lung cancer (NSCLC) ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“… 27 In addition, several studies have shown the favorable efficacy of anti-angiogenic drugs in the treatment of advanced NSCLC. 26 , 28 33 To date, however, very few studies have confirmed the effect of anti-angiogenic drugs on the severity of COVID-19 in patients with NSCLC. To address this gap, we conducted this study to investigate the impact of anti-angiogenic drugs on COVID-19 severity in patients with NSCLC.…”
Section: Introductionmentioning
confidence: 99%